Disarming the Host: Detoxification of Plant Defense Compounds During Fungal Necrotrophy - Westrick, Nathaniel M.; Smith, Damon L.; Kabbage, Mehdi (Frontiers in Plant Science, 2021)
While fungal biotrophs are dependent on successfully suppressing/subverting host defenses during their interaction with live cells, necrotrophs, due to their lifestyle are often confronted with a suite of toxic metabolites. These include an assortment of plant defense compounds (PDCs) which can demonstrate broad antifungal activity. These PDCs can be either constitutively present in plant tissue or induced in response to infection, but are nevertheless an important obstacle which needs to be overcome for successful pathogenesis. Fungal necrotrophs have developed a number of strategies to achieve this goal, from the direct detoxification of these compounds through enzymatic catalysis and modification, to the active transport of various PDCs to achieve toxin sequestration and efflux. Studies have shown across multiple pathogens that the efficient detoxification of host PDCs is both critical for successful infection and often a determinant factor in pathogen host range. Here, we provide a broad and comparative overview of the various mechanisms for PDC detoxification which have been identified in both fungal necrotrophs and fungal pathogens which depend on detoxification during a necrotrophic phase of infection. Furthermore, the effect that these mechanisms have on fungal host range, metabolism, and disease control will be discussed.